Proceedings of the International Conference on Nanomedicine (ICON-2019) - Rajan, Mariappan; Anand, Krishnan; Chuturgoon, Anil.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the Proceedings of ICON-2019, an international meeting exclusively dedicated to nanostructured materials in medicinal applications. The conference emphasized the recent advances in multidisciplinary research on processing, morphol¬ogy, structure and properties of nanostructured materials and their applications in vari¬ous medicinal fields. The papers encompass basic studies and applications and address topics of novel issues, difficulties, and breakthroughs in the field of nanomedicine in cancer, tuberculosis, tissue engineering, regenerative medicine etc.
Nanotechnology In Civil Infrastructure -- Phytosynthesis of Silver Nanoparticles Using Rhynchosia Heynei Wight & Arn Leaf Extract: Characterization and In Vitro Assessment Of Antimicrobial, Antioxidant and Anticancer Activities -- A Facile Route for the Fabrication of Nanocompositie by Effective Impregnation through the Biopolymer Matrix and Its Characterisation -- Green Synthesis of Silver Nanoparticles from De-Oiled Rhizomes of Curcuma Longa L. and Its Biomedical Potential -- Drug Loaded Chitosan / Aloe Vera nanocomposite on Ti for Orthopedic Applications -- In-Vitro Wound Healing and Release Kinetics of β- Cyclodextrin Encapsulated Curcumin Loaded Carrageenan Hydrogel Film: An Efficient Wound Dressing Material -- Anti-Bacterial Activity of Herbo Mineral Nano Preparation -- Acoustical and Excess Properties on Ternary Liquid Mixtures of Ortho Methoxy Phenol, 1 Butanol and N- Hexane at Different Temperatures -- Synthesis and Characterisation Studies of Zno and Its Antimicrobial Activity -- One Step Synthesis of Reduced And Moringa Oleifera Treated Graphene Oxide: Characterization And Antibacterial Studies -- Inhibition of C-Steel Corrosion in Acid Medium by Cassia Javancia Leaves Extract -- Precision Medicine: A Personalized Treatment from Your Gene -- Encapsulation of Amphotericin B into Quercetin Based Silver Nanoparticles: Preparation, Characterization and Preliminary Investigation of Antiparasitic Activity -- Apoptotic Activity In Cervical Cancer Hela Cell Lines Treated With Chitosan Nanoconjugated Drug Doxorubicin - As Nanocarrier For Drug Delivery -- Doxorubicin Encapsulated ZIF-8 Nanoparticles For Anticancer Applications -- The Impact of Gold Nanoparticles with Low Energy Irradiation Treatment Ontemperature Induction and Cell Viability of Breast Cancer Cell -- Green Synthesis of Silver Nanoparticles Using Ledebouria Revoluta Bulb Extractand Its Biological Activity -- Ultrasonic Studies on Molecular Interaction and Their Excess Properties of Ternary Liquid Mixtures of 2-Nitroanisole And 1- Propanol In N-Hexane At Different Temperatures 303, 308 and 313k -- Thermal And Physical Properties Of Some Deep Eutectic Solvents -- Dual Delivery of Antibiotic and Antiresorptive Drugs by Hydroxyapatite-Chitosan Composite Nanocarrier for the Treatment of Osteomyelitis.
Keywords: Nanotechnology; Biomaterials; Regenerative medicine; Nanotechnology; Biomaterials; Regenerative Medicine and Tissue Engineering